The Good Lives Model: A strength-based approach for youth offenders. (January 2018) - Fortune, Clare-Ann
Abstract: There is increasing interest in the use of strength-based approaches, such as the Good Lives Model (GLM), in the field of offender rehabilitation to complement primarily risk management models. To date, theoretical work has focused on the application of the GLM to adult offenders, and primarily sexual offenders at that. This paper explores the theoretical application of the Good Lives Model (GLM) to the rehabilitation of youth offenders. Practitioners often struggle to engage young people in treatment as working towards the goal of avoiding further offending does not directly speak to their core concerns and, as such, is not very motivating. The GLM is a rehabilitation framework that focuses on approach goals, which encourages individuals to identify and formulate ways of achieving personally meaningful goals in prosocial ways. It is argued that as a rehabilitation framework the GLM has the flexibility and breadth to accommodate the variety of risk factors and complex needs youth offenders present with, and also provides a natural fit with a dynamic systems (e.g., family and educational systems) framework, and evidence based interventions in the youth offender field.